2021
DOI: 10.3390/jcm10092028
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Rhabdomyosarcoma: Epidemiology and Genetic Susceptibility

Abstract: Rhabdomyosarcoma (RMS) is the most common soft-tissue sarcoma in children, yet little is known about its etiology. Studies that examine either environmental exposures or germline genetic predisposition in RMS have begun to identify factors that contribute to this malignancy. Here, we summarize epidemiological reports of RMS incidence in terms of several factors, including age at diagnosis, biological sex, and geographic location. We then describe findings from association studies, which explore the role of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 101 publications
0
45
0
1
Order By: Relevance
“…35 In rhabdomyosarcoma, nominal enrichment signal was observed for TP53 and DICER1, genes that have previously been implicated in germline predisposition to pediatric rhabdomyosarcoma. 36 We were able to redemonstrate a nominal enrichment signal for BRCA2 (MIM: 600185), a gene with a previous moderate level of evidence for a role in germline predisposition to rhabdomyosarcoma. 33,[37][38][39] We also observed a nominal enrichment signal in SDHD (MIM: 602690); pathogenic germline variants in succinate dehydrogenase complex genes have been reported in rhabdomyosarcoma and other sarcoma subtypes before.…”
Section: Ancestry Composition Of Discovery Cohortmentioning
confidence: 83%
“…35 In rhabdomyosarcoma, nominal enrichment signal was observed for TP53 and DICER1, genes that have previously been implicated in germline predisposition to pediatric rhabdomyosarcoma. 36 We were able to redemonstrate a nominal enrichment signal for BRCA2 (MIM: 600185), a gene with a previous moderate level of evidence for a role in germline predisposition to rhabdomyosarcoma. 33,[37][38][39] We also observed a nominal enrichment signal in SDHD (MIM: 602690); pathogenic germline variants in succinate dehydrogenase complex genes have been reported in rhabdomyosarcoma and other sarcoma subtypes before.…”
Section: Ancestry Composition Of Discovery Cohortmentioning
confidence: 83%
“…Rhabdomyosarcoma (RMS) is another sarcoma classically driven by a fusion protein and exhibits strong LSD1 overexpression. RMS is the most common soft tissue sarcoma in children, and is subdivided into alveolar and embryonal rhabdomyosarcoma based on the histological makeup of the tumor ( 66 ). About 31% are alveolar and present with an alveolar pattern on histology, and 58% are embryonal with sheets and nests on histology, while the remaining 11% are made up of smaller subtypes with other histological patterns ( 66 ).…”
Section: Lsd1 In Sarcomasmentioning
confidence: 99%
“…Other authors have shown that DICER1 variants, either somatic or germline, occur almost ubiquitously across all uterine embryonal RMS [21] . The majority of DICER1-associated RMS have been reported in the female genitourinary tract, but an association with ERMS outside of this body system is emerging [22,23] .…”
Section: Rhabdomyosarcomamentioning
confidence: 99%